Respuesta :

Answer:

They all need to be equal in both sides.

Step-by-step explanation:

a) sqrt(x^12)=x^6

Take the square root --> x^6=x^6

b) sqrt(x^2-12x+36)=6-x

Factor --> sqrt((x-6)(x-6))=6-x

Take the square root --> x-6 = to 6-x

This is true since the square root gives you always a positive and a negative answer.

c) sqrt(x^4+2x+1)=x^2+1

Factor --> sqrt((x^2+1)(x^2+1))=x^2+1

d)sqrt((x^2)/4+2x+4)= -(x)/2-2

Simplify Factoring: In this part you can use the Quadratic Formula.

--> sqrt((x/2+2)^2)=-(x)/2-2

Take the square root --> (x/2)+2=-(x)/2-2

This is true since the square root gives you always a positive and a negative answer.